ประสบการณ์การเป็นพี่เลี้ยงของพยาบาลวิชาชีพในโรงพยาบาลมหาวิทยาลัยของรัฐ - มาเรียม เพราะสุนทร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this qualitative study was to explain the mentoring work as experienced by professional nurses. Sixteen professional nurses were willing to participate in this study. In-depth interview, non-participant observation and other documents were employed for data collection .Study data were analyzed by using coding and constant comparative method. The core category of this study was " a mentoring process" consisting of 6 categories: (1) being assigned to be a mentor, (2) preparing as a mentor, (3) getting to know each another, (4) acting as a mentor, (5) getting feedback, and ending mentor’s roles. According to study findings, the mentoring process began when a head nurse assigned nurses to be a mentor for a novice. Some were assigned immediately to take a mentor’s role but some had time to prepare themselves and got to know a novice before acting as a mentor. The feedback were given twice (after daily duty and the end of mentorship) in order to improve mentor’s roles. After the end of mentoring process, the mentor reported either positive or negative experiences. Mentoring process would start again when a nurse was assigned to be a mentor.